Synthesis, Characterisation, Photocatalytic Activity, and Aquatic Toxicity Evaluation of TiO2 Nanoparticles - Andronic, Luminita; Vladescu, Alina; Enesca, Alexandru (Nanomaterials (Basel, Switzerland), 2021)
Imidacloprid (IMD) is a toxic pesticide, and is one of the eight most widely used pesticides globally. Heterogeneous photocatalysis has often been investigated in recent years and can be successfully applied to remove imidacloprid from water. However, less investigated is the toxic effect of both the photocatalyst and the pesticide on aquatic life. Titanium dioxide (TiO2) remains the most effective photocatalyst, provided it is not toxic to the aquatic environment. This study investigated the TiO2 synthesis, characterisation, and photocatalytic activity on imidacloprid degradation and the toxicity of TiO2 nanoparticles and imidacloprid on the green algae Chlorella vulgaris. In the photodegradation process of IMD (initial concentration of 20 mg/L), electrons play an essential role; the degradation efficiency of IMD after 6 h increased from 69 to 90% under UV irradiation when holes (h+) scavengers were added, which allowed the electrons to react with the pollutant, resulting in lowering the recombination rate of electron-hole charge carriers. Growth inhibition of Chlorella vulgaris and effective concentration (EC50) were determined to study the toxic effect of TiO2 nanoparticles and imidacloprid. The EC50 increased from 289.338 mg/L in the first 24 h to 1126.75 mg/L after 96 h Chlorella vulgaris algal age, when the toxicant was TiO2. When IMD was the aquatic toxicant, a decrease in EC50 was observed from 22.8 mg/L (24 h) to 0.00777 mg/L (120 h), suggesting a long-term high toxicity level when pesticides in low concentrations are present in an aquatic environment.